2017
DOI: 10.1080/09544828.2016.1274719
|View full text |Cite
|
Sign up to set email alerts
|

Supporting the development of shared understanding in distributed design teams

Abstract: Distributed teams are an increasingly common feature of engineering design work. One key factor in the success of these teams is the development of short- and longer-term shared understanding. A lack of shared understanding has been recognized as a significant challenge, particularly in the context of globally distributed engineering activities. A major antecedent for shared understanding is question asking and feedback. Building on question-asking theory this work uses a quasi-experimental study to test the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(57 citation statements)
references
References 67 publications
3
54
0
Order By: Relevance
“…Despite prior studies' emphasis on the use of visual representations (e.g. sketches, drawings, CAD models) as means to communicate (Hietikko and Rajaniemi 2000;Goldschmidt 2007) and establish shared understanding (Carlile 2002;Marheineke, Habicht, and Möslein 2016;Cash, Dekoninck, and Ahmed-Kristensen 2017), research has mostly been conducted in co-located cross-functional NPD contexts. As claimed by Lindlöf (2014, 75), there is a need for the 'design of boundary objects for communication in geographically distributed teams'.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite prior studies' emphasis on the use of visual representations (e.g. sketches, drawings, CAD models) as means to communicate (Hietikko and Rajaniemi 2000;Goldschmidt 2007) and establish shared understanding (Carlile 2002;Marheineke, Habicht, and Möslein 2016;Cash, Dekoninck, and Ahmed-Kristensen 2017), research has mostly been conducted in co-located cross-functional NPD contexts. As claimed by Lindlöf (2014, 75), there is a need for the 'design of boundary objects for communication in geographically distributed teams'.…”
Section: Discussionmentioning
confidence: 99%
“…Hinds and Bailey 2003;Hinds and Mortensen 2005). According to Cash, Dekoninck, and Ahmed-Kristensen (2017), the lack of proximity also reduces the possibility for visual observation and informal contact, hence constrains learning across locations. Shared references to objects of interest are thus more challenging to establish, which might in turn obstruct effective communication on work tasks Ceci and Prencipe 2013).…”
Section: Communication Challenges and Use Of Visual Representationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tomasello observed infants' behaviour and found that intersubjectivity is not only responsive to other subjects' goals, but also the means employed in achieving those goals (Tomasello, 2008). There is a recent experimental study, which captures shared understanding among team members during collaboration (Cash et al, 2017), but shared understanding is not based on intersubjectivity among members, but on each member's independent subjectivity. In this paper, the authors propose a methodology to evaluate intersubjectivity being formed among individuals and indicate knowledge obtained from an experimental study focused on relationships between intersubjectivity and the collaborative process.…”
Section: Intersubjectivitymentioning
confidence: 99%
“…It is also lamentable to see collaborative projects wound up when the given framework is taken away, for instance, facing a loss of resources, becoming obsolete in dynamic circumstances, or the termination of a period of subsidy. Regardless the fields applied, there have been substantial studies on the collaboration process from the points of view of knowledge sharing, knowledge integration and shared understanding in established teams (Maier et al, 2009;Gendron et al, 2012;Kleinsmann et al, 2012;Yang et al, 2012;Cash et al, 2017). However, these are not enough to understand co-creative collaboration since it requires more consideration of internal human factors than co-operative collaboration.…”
Section: Introductionmentioning
confidence: 99%